Reconstruction of Economic Policies in Islamic Education Based on Pesantren Self-Reliance in the Society 5.0 Era - Sari, Linda Nevia; Asha, Lukman; Fakhruddin, Fakhruddin (The Future of Education Journal, 2025)
Technological advancements in the era of Society 5.0 present new challenges for the world of Islamic education, particularly for pesantren, which have long been known for their independence. Pesantren not only function as religious education institutions but also have significant potential as a foundation for strengthening the economic empowerment of the community. This study aims to explore and formulate the direction of the reconstruction of Islamic education economic policies that can strengthen the independence of pesantren in facing the dynamics of the digital society. Using a qualitative approach through library research, this article examines various relevant concepts and policies, as well as the potential integration of pesantren values with technological developments. The analysis shows that the independence of pesantren can be strengthened through the development of entrepreneurship among students, the digitalization of pesantren business units, and strategic collaboration with various stakeholders. This policy reconstruction, which focuses on economic independence, is expected to encourage pesantren to become adaptive and contributive institutions in national development based on Islamic values.